MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER PADA MATA PELAJARAN IPA KELAS VIII B SMPN 5 SUKADANA - Rahmayani, Cici; Ningsih, Kurnia; Wahyuni, Eko Sri (Universitas Tanjungpura, 2025)
The use of learning models is beneficial in enhancing student learning activities. The aim of this study was to improve students' learning activities by applying the cooperative learning model of the Numbered Heads Together (NHT) type in the science subject for class VIII B at SMPN 5 Sukadana. This research is a classroom action research (CAR). The study consists of four stages: planning, implementation, observation, and reflection. The subjects of this research were 25 students, consisting of 13 female and 12 male students from class VIII B at SMPN 5 Sukadana in the 2024/2025 academic year. The instrument used was an observation sheet. The data collection techniques employed were observation and documentation. The results of the study on learning activities showed that in cycle I, the percentage was 82.4%, and in cycle II, it increased to 92.8%. The findings indicate that the use of the cooperative learning model of the Numbered Heads Together type can improve students' learning activities in science subject for class VIII B at SMPN 5 Sukadana.